Bimbingan Teknis Manajemen Perkoperasian bagi Pengurus Koperasi Kota Cimahi: Pengembangan Jaringan Usaha Koperasi - Gijanto Purbo Suseno (E-Coops-Day, 2023)
One of the efforts to improve the performance of cooperative businesses is to develop cooperative business networks. Business progress will be more compatible if carried out in synergy through collaboration with other parties. Thus, cooperative human resources, especially administrators, are required to be able to implement the development of cooperative business networks. One of the efforts to improve the human resources of this cooperative is to provide technical guidance. For this purpose, the Cimahi Cooperative Office conducted Cooperative Technical Guidance activities, in order to improve the competence of cooperative administrators in their working area. Specifically for the material for developing cooperative business networks, the Bimtek method used is lectures, discussions, questions, and answers as well as case study. The training participants were cooperative administrators in the working area of the Cimahi. Participants were quite motivated in participating in this activity. Several cooperatives have started to pioneer and implement the development of business networks. The understanding of the Bimtek participants was quite good. Follow-up on technical guidance needs to be carried out, one of which is by providing assistance to Bimtek participants in its implementation, as well as conducting an evaluation at least three months after the technical guidance.